If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13q + 48 = -3q Reorder the terms: 48 + 13q = -3q Solving 48 + 13q = -3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '3q' to each side of the equation. 48 + 13q + 3q = -3q + 3q Combine like terms: 13q + 3q = 16q 48 + 16q = -3q + 3q Combine like terms: -3q + 3q = 0 48 + 16q = 0 Add '-48' to each side of the equation. 48 + -48 + 16q = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 16q = 0 + -48 16q = 0 + -48 Combine like terms: 0 + -48 = -48 16q = -48 Divide each side by '16'. q = -3 Simplifying q = -3
| -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= | | 2x-39=21 | | 8t+1=-7 | | 3(-12)-6=42 | | 50=x+y*2x | | 9-4z=1 | | -3x+8=56+5x | | -19=19+19b | | X+124+x+74=180 | | 1.25-7=53.1 | | 3(16)-6=42 | | 4x+34+90=3x | | x-3+10+x-10+2+8= | | 6+2d=18 | | -5(8+4d)-9d= | | 168=-8(4m+7) | | 0=xsin(0.5x)-2cos(0.5x) | | 6x+2=42 | | 3(x-6)=6x+24 | | 4n-14=82 | | 1+4y=9 | | 3u-6=-42 | | 9x=-60 | | 3x+2+6x-13=5x | | 198=3(2+8x) | | 7-x+7x=79 |